First Record of the Boreal-Arctic Marine Leech Mysidobdella Borealis (Hirudinida, Piscicolidae) from the Southern Bay of Biscay - Utevsky, S.; Sorbe, J. (Vestnik Zoologii, 2012)
Four individuals of the marine fish leech Mysidobdella borealis (Johansson,1898) were sampled from the mysids Schistomysis parkeri Norman, 1892 from the swash zone of Hendaye beach, France. This is the only known so far boreal-arctic piscicolid species occurring from the southern Bay of Biscay to the Kara Sea